2013
DOI: 10.1002/adma.201204555
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Reconstructions at the LaAlO3/SrTiO3 Interface

Abstract: The physics of transition metal oxide heterostructures is a subject of great interest due to the observations of new interface electronic and magnetic states. [ 1 ] The two-dimensional electron gas (2DEG) discovered at the interface between insulating LaAlO 3 (LAO) thin fi lms and bulk SrTiO 3 (STO) crystals stands as a model and has boosted the great expectations placed in oxide electronics. [ 2 , 3 ] Recently, it has been found that also the (001) SrTiO 3 surfaces, obtained by cleaving SrTiO 3 in ultra-hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 31 publications
27
87
0
Order By: Relevance
“…In particular, for each La(Sr) or Al(Ti) exchange, the interface will get both donor and acceptor levels (thus electron and holes) which are expected to be annihilated being located essentially at the same place. Note that cation intermixing were observed by high-resolution transmission electron microscopy (HRTEM) [54] and by grazing incidence surface diffraction (GXID) by several groups on samples grown in different laboratories [37,55]. As matter of fact the degree of La/Sr and Al/Ti substitution was found dependent on the growth conditions, the sample thickness, and varied from sample to sample.…”
Section: Other Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, for each La(Sr) or Al(Ti) exchange, the interface will get both donor and acceptor levels (thus electron and holes) which are expected to be annihilated being located essentially at the same place. Note that cation intermixing were observed by high-resolution transmission electron microscopy (HRTEM) [54] and by grazing incidence surface diffraction (GXID) by several groups on samples grown in different laboratories [37,55]. As matter of fact the degree of La/Sr and Al/Ti substitution was found dependent on the growth conditions, the sample thickness, and varied from sample to sample.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…These results were confirmed in ref. [37], where it was shown that below 4 uc, i.e. in nominally 2 uc LAO/STO films, the LAO layers are strongly rumpled, indicating the presence of an internal electric field, and the unit cells are expanded in a direction perpendicular to the interface.…”
Section: The Electronic Reconstruction Mechanismmentioning
confidence: 99%
See 3 more Smart Citations